2000
DOI: 10.1128/mcb.20.1.286-298.2000
|View full text |Cite
|
Sign up to set email alerts
|

Essential Function of the Polo Box of Cdc5 in Subcellular Localization and Induction of Cytokinetic Structures

Abstract: Members of the polo subfamily of protein kinases play pivotal roles in cell proliferation. In addition to the kinase domain, polo kinases have a strikingly conserved sequence in the noncatalytic C-terminal domain, termed the polo box. Here we show that the budding-yeast polo kinase Cdc5, when fused to green fluorescent protein and expressed under its endogenous promoter, localizes at spindle poles and the mother bud neck. Overexpression of Cdc5 can induce a class of cells with abnormally elongated buds in a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
178
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(185 citation statements)
references
References 53 publications
7
178
0
Order By: Relevance
“…Consistent with the structural and functional similarities to Plk1, yeast Plks exhibit strong localization to the spindle pole bodies (SPBs) but with apparent differences in timing. Cdc5 localizes to the SPBs (Shirayama et al, 1998;Song et al, 2000) as early as in G1 and remains there until late mitosis (Figure 2), whereas Plo1 associates with the SPBs after the activation of Cdc2 (Cdk1) and dissociates from the SPBs as Cdc2 becomes inactive (Mulvihill et al, 1999). Although weak Plo1 localization has been detected at the spindles (Bahler et al, 1998;Mulvihill et al, 1999), yeast Plks do not appear to localize to the spindle midzone.…”
Section: Subcellular Localization and The Polo-box Domainmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with the structural and functional similarities to Plk1, yeast Plks exhibit strong localization to the spindle pole bodies (SPBs) but with apparent differences in timing. Cdc5 localizes to the SPBs (Shirayama et al, 1998;Song et al, 2000) as early as in G1 and remains there until late mitosis (Figure 2), whereas Plo1 associates with the SPBs after the activation of Cdc2 (Cdk1) and dissociates from the SPBs as Cdc2 becomes inactive (Mulvihill et al, 1999). Although weak Plo1 localization has been detected at the spindles (Bahler et al, 1998;Mulvihill et al, 1999), yeast Plks do not appear to localize to the spindle midzone.…”
Section: Subcellular Localization and The Polo-box Domainmentioning
confidence: 97%
“…These results suggest that the polo-box is critical for targeting the catalytic activity of Plk1 to specific subcellular locations and that this step is required for Plk1 function. Analogous mutations in the PB1 impaired both the localization and mitotic functions of Cdc5 and Plk1 in their native organisms (Song et al, 2000;Seong et al, 2002). Thus, the role of the polo-box domain (PBD) is conserved in various eucaryotic organisms.…”
Section: Subcellular Localization and The Polo-box Domainmentioning
confidence: 99%
“…Considering that the consensus for PBD binding fulfills the requirements for phosphorylation by Proline-directed kinases such as Cdks and MAP kinases, it has been suggested that the latter may act as priming factors for Plk1 targeting [70]. The PBD has two established functions: it constitutes an autoinhibitory domain [72] whose negative role is relieved through phosphorylation at the T-loop site T 210 [73] (see below), and it plays an important role in Plk1 subcellular localization [74]. The latter was elucidated in complementation studies conducted on the temperaturesensitive cdc5-1 mutant yeast strain, where mutation of conserved residues in the PBD disrupted localization and mitotic functions of human Plk1, without nonetheless altering catalytic activity [75].…”
Section: Polo-like Kinasementioning
confidence: 99%
“…(b) An unrooted tree shows the distance relationship between Plks from organisms containing only a single Plk family member (Polo, Plo1, Cdc5) from other members of the Plk family Structure and function of Polo-like kinases DM Lowery et al 1998; Logarinho and Sunkel, 1998;Qian et al, 1999), perhaps facilitating microtubule sliding or some aspect of kinetochore dynamics (Lee et al, 1995), and eventually come to flank the central portion of the cytokinetic bridge (i.e. the midbody) during telophase and cytokinesis (Golsteyn et al, 1994;Lee et al, 1995;Moutinho-Santos et al, 1999;Qian et al, 1999;Song et al, 2000). At least for Cdc5, a portion of the protein is localized at the future site of cytokinesis (the bud neck in budding yeast) from late G 2 onward (Sakchaisri et al, 2004), indicating that Plks may be involved in organizing the structures that will eventually result in cytokinesis.…”
Section: Function Of the Pbdmentioning
confidence: 99%